Performance Comparison of Large-Core Optical Waveguides with Waste-Derived and Analytical-Grade Chitosan Core Materials - Yulianti, Ian; Rizkika, Aflah Agus; Darma Putra, Ngurah Made; Alauhdin, Mohammad; Astuti, Budi; Wiwit Prayitno, Wasi Sakti; Prayogo, Deffrian; Mufatihah, Nishfa; Athoriq, Naufal (Diponegoro University Semarang Indonesia, 2026)
This study investigates and compares the optical performance of large-core polymer waveguides fabricated using shrimp-shell-derived chitosan (SSC) and analytical-grade chitosan (AGC) as core materials. Both materials were processed into a buried square-core waveguide configuration and evaluated through optical loss measurements, time-dependent loss (TiDL), temperature-dependent loss (TDL), and microstructural examination. The two chitosan types exhibited their lowest attenuation at a concentration of 0.04 g/mL, with AGC showing marginally lower optical loss, consistent with its higher purity and degree of deacetylation. AGC also demonstrated superior temporal and thermal stability, supported by SEM results indicating a smoother and more homogeneous core morphology. Nevertheless, SSC showed performance levels closely comparable to AGC, revealing that biowaste-derived chitosan can function effectively as a core material for large-core waveguides. This outcome underscores the potential of SSC as a sustainable, low-cost alternative, contributing to SDG 12 (Responsible Consumption and Production) through biowaste valorization, and SDG 9 (Industry, Innovation, and Infrastructure) by promoting eco-friendly materials for future optical sensor platforms. The results affirm that SSC-based waveguides hold promise for applications including humidity, pH, chemical, and biochemical sensing.